Rethinking the Relevance of Magic Realism for English-Canadian Literature: Reading Ann-Marie MacDonald’s Fall On Your Knees - Andrews, Jennifer (Studies in Canadian Literature, 1999)
Canadian magic realist texts are often identified with postcolonialism and postmodernism. Ann-Marie MacDonald's Fall On Your Knees provocatively reworks the formal and thematic dimensions of magic realism by presenting a story of a mixed-race Cape Breton family from a lesbian feminist perspective, demonstrating that the Maritimes can be a viable setting for magic realist works. Through her magic realist treatment of characters, MacDonald begins to explore the race, gender and sexual politics that exist both within the Piper family and the community at large. Fall On Your Knees displays a heightened awareness of other literary texts and cultivates a consciously metafictional approach to the writing of fiction. The novel combines an exploration of the nature and limits of the knowable and a playful recreation of history with a realistic presentation of specific political concerns.